Sosialisasi Kewirausahaan Pembuatan Telur Gulung Pada Siswa Kelas VI SDN 48 Kota Bengkulu - Juniar, Intan; Soleh, Ahmad; Putra, Iswidana Utama; Astuti, kamelia; Yulianti, Oni (Universitas Dehasen Bengkulu, 2024)
Entrepreneurship is creating something that adds value and makes a profit. This is done by an individual or group to manage a business. Entrepreneurship can be interpreted as encouraging entrepreneurial actors to take risks by being creative and adapting in the face of continuous changes in the future.This community service activity aims to inform class VI students of SDN 48 BENGKULU CITY about how to become successful and creative entrepreneurs to be able in this sophisticated era. This activity explains what entrepreneurship is, how to become a creative entrepreneur and how to create an initial concept for starting a business, examples of products to market, ways to make products, good marketing strategies. It is hoped that with this, students at SDN 48 KOTA BENGKULU will understand entrepreneurship better and be more interested in business so that in the future they can open successful businesses and help create jobs for local people.